Time of onset, location, and duration of lameness in beef cattle in a commercial feedyard - Green, T.M.; Guichon, P.T.; Thomson, Daniel U.; Wileman, Benjamin W.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Bovine lameness presents itself in a variety of forms. A number of predisposing factors have been reported, such as increased amounts of wet feces and mud from high rainfall; limb trauma from rocks, sticks, or handling facilities; inappropriate animal handling; or improper facility design. Trauma causes lameness directly and often provides an avenue for bacterial agents to enter and colonize a wound. Performance of lame cattle is diminished due to impaired ambulation, resulting in decreased feed intake and decreased body weight. The objective of this study was to determine the timing of the onset of lameness in feeder cattle and to determine the association between lameness and feedlot performance.
Keywords: Beef; Lameness; Feedlot; Performance